Global Cancer Risk From Unregulated Polycyclic Aromatic Hydrocarbons. (23rd September 2021) - Kelly, Jamie M.; Ivatt, Peter D.; Evans, Mathew J.; Kroll, Jesse H.; Hrdina, Amy I. H.; Kohale, Ishwar N.; White, Forest M.; Engelward, Bevin P.; Selin, Noelle E.
Abstract: In assessments of cancer risk from atmospheric polycyclic aromatic hydrocarbons (PAHs), scientists and regulators rarely consider the complex mixture of emitted compounds and degradation products, and they often represent the entire mixture using a single emitted compound—benzo[a]pyrene. Here, we show that benzo[a]pyrene is a poor indicator of PAH risk distribution and management: nearly 90% of cancer risk worldwide results from other PAHs, including unregulated degradation products of emitted PAHs. We develop and apply a global‐scale atmospheric model and conduct health impact analyses to estimate human cancer risk from 16 PAHs and several of their N‐PAH degradation products. We find that benzo[a]pyrene is a minor contributor to the total cancer risks of PAHs (11%); the remaining risk comes from other directly emitted PAHs (72%) and N‐PAHs (17%). We show that assessment and policy‐making that relies solely on benzo[a]pyrene exposure provides misleading estimates of risk distribution, the importance of chemical processes, and the prospects for risk mitigation. We conclude that researchers and decision‐makers should consider additional PAHs as well as degradation products. Plain Language Summary: Nearly 90% of global human lung cancer risk from polycyclic aromatic hydrocarbons (PAHs) comes from compounds omitted by prior analyses and not regulated directly. PAHs in the atmosphere are a complex mixture, but regulators and researchers often represent them using a single compound, namely benzo(a)pyrene. We show that benzo(a)pyrene is a poor indicator of global PAH cancer risk; its use as a proxy leads to erroneous conclusions about high‐risk populations and atmospheric chemical processes. We find that approximately 17% of risk comes from PAHs that are produced in atmospheric reactions and are not regulated or routinely monitored. Regulators and researchers should focus on the entire mixture of PAHs in the atmosphere, and we recommend that benzo(a)pyrene not be used as a sole reference compound. Key Points: Benzo[a]pyrene is a small contributor to human cancer risk of polycyclic aromatic hydrocarbons (PAHs) worldwide (11%) Using benzo[a]pyrene as a surrogate compound leads to erroneous conclusions about high‐risk populations and the importance of uncertain chemical processes Science and policy could be improved by considering a wider group of both emitted PAHs as well as their degradation products